Development of RF spectrum management tool for Malaysia using Open-Source software - Saman, Mohamad Afif; Ismail, Ahmad Fadzil; Mohd. Ramli, Huda Adibah; Badron, Khairayu; Hashim, Wahidah (ETPub, 2014)
In recent years, mobile communications technologies have evolved rapidly. A lot of countries including Malaysia have adopted these technologies once they are available. This increases the number of subscribers and services in cellular network. It forces new installation of cellular base stations (BS) in order to improve coverage. This however increased the likelihood of interference between BS which will reduce network efficiency. Thus, it is needed to develop a Radio Frequency (RF) spectrum monitoring tool that not only can identify interference before any new BS installation but also monitor interference between existing BS. The tool’s database needs to contain data on BS, their location as well as its respective allocated frequency so that interference could be determined promptly. Expensive commercial spectrum management tool led us to seek low cost solution. This paper aims to outline the approaches taken in developing a spectrum management tool for Malaysian authority. The tool is currently being devised using an open source Geographical Information System software. The end result will be a simple low cost tool that not only can identify interference but also display the coverage area of BS; which all in all can be very useful and practical for spectrum management process